Metaleisure: Leisure Time Habits to be Changed with Metaverse - Alican Bayram (Journal of Metaverse, 2022)
New habits that will come into our lives with a metaverse will create the concept of Metaleisure. With the introduction of virtual platforms into our lives, the mass of people spending their leisure time on the Internet grew. This group participates in many leisure time activities on virtual platforms, defined as the concept of electronic leisure (e-leisure). The metaverse has taken this electronic participation to a whole different dimension. The metaverse has initiated the process of being involved in leisure time activities in three-dimensional environments through avatars. The purpose of this article was to conceptualize the concept of metaleisure as a new leisure time habit that enters our lives with the metaverse and discuss this theory. This study provides researchers, who conduct studies on metaverse and leisure time, with the characteristics to understand the time frame spent with the metaverse. Leisure time users are an important resource for the metaverse industry. Games, museums, and concerts are the leading examples. E-idle stands out as an important factor pointing to the consumption of leisure time participants in the game industry. The concept of metaleisure will become important for leisure time research as well. In order to understand leisure time behavior, it is necessary to be able to interpret changing habits and technological development. As a result, the concept of metaleisure is defined as leisure time activities that individuals perform in three-dimensional universes through avatars. With the development of wearable technology, the interest of metaleisure participants in this new universe will grow. With the spread of metaleisure, traditional leisure time activities will gradually become retro leisure time activities.